Peta Risiko Bencana sebagai Instrumen Partisipatif Pemberdayaan Masyarakat dalam Mitigasi Longsor - Nurdin, Ananda Risky; Paranti, Lesa (Jurnal Abdi Negeri, 2025)
This community service program aimed to reduce landslide risk in Kandri Village, Gunungpati District, Semarang City, by utilizing a participatory disaster risk map as the main instrument for community empowerment. The risk assessment revealed that land movement is the highest threat with a score of 6 (probability = 3, impact = 3), compared to fire (3), drought (2), and land exploitation (2). The high risk is caused by a combination of hilly topography, high rainfall, clay soil, and human activities such as deforestation and hillside construction. Methods included FGDs, participatory mapping, awareness campaigns, preparedness training, and evacuation drills. As a result, the community was able to read and use the risk map to identify vulnerable areas (RW 2 and RW 4), designate evacuation routes, and develop a local early-warning system. The risk map proved effective as both an educational medium and a practical tool in building a Disaster-Resilient Village.